The effect of soybean extract supplementation to tris aminomethane–egg yolk extender on the post-thawing quality of Simmental semen - Sri Wahjuningsih; Muhammad Nur Ihsan; Aulia Puspita Anugra Yekti; Muhammad Agus Tahar (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2020)
This research aims to evaluate the effect of soybean extract (Glycine max (L.) Merr.) supplementation on tris aminomethane egg yolk extender to the post thawing quality of Simmental bull frozen semen. The fresh semen was collected from 3 Simmental bulls aged at 3 to 3.5 years for twice a week by using artificial vagina. The semen was then selected for sperm motility and abnormality, and the semen that had >70% motility and <15% abnormality was used for the research. The research was conducted in a completely randomized with 4 treatments and 30 replications. The research treatments include 0% (T0), 7.5% (T1), 10% (T2), and 12.5% (T3) soybean extract supplementation on tris aminomethane egg yolk extender. The observed variables include spermatozoa motility, viability, abnormality, and plasm membrane integrity. The collected data were analysed with ANOVA and followed with Duncan’s Multiple Range Test to determine significant differences. The results showed that soybean extract supplementation gave significant effect (P<0.05) to the post thawed quality of Simmental semen. The research concludes that 10% (v/v) soybean  supplementation on tris aminomethane egg-yolk extender was effective to maintain sperm motility, viability, and plasma membrane integrity of post thawed Simmental semen.